2010
DOI: 10.1111/j.1600-0897.2010.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW ARTICLE: Immunological Modes of Pregnancy Loss

Abstract: Citation Kwak‐Kim J, Park JC, Ahn HK, Kim JW, Gilman‐Sachs A. Immunological modes of pregnancy loss. Am J Reprod Immunol 2010During the implantation period, a significant portion of embryos are lost and eventually less than half of clinically established pregnancies end as full‐term pregnancies without obstetrical complications. A significant portion of these pregnancy losses is associated with immune etiologies, including autoimmune and cellular immune abnormalities. Although an autoimmune etiology such as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 119 publications
(101 reference statements)
1
82
0
6
Order By: Relevance
“…It has been reported that during the implantation period, a significant number of embryos are lost, and less than half of clinically established pregnancies eventually carry to full term without obstetric complications (Kwak-Kim et al, 2010). In this study, it was shown that most SAs and RSAs occurred soon after implantation, before the development of the fetal cardiac system as evidenced by the description of fetuses with empty gestational sacs and fetal poles without fetal cardiac activity.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It has been reported that during the implantation period, a significant number of embryos are lost, and less than half of clinically established pregnancies eventually carry to full term without obstetric complications (Kwak-Kim et al, 2010). In this study, it was shown that most SAs and RSAs occurred soon after implantation, before the development of the fetal cardiac system as evidenced by the description of fetuses with empty gestational sacs and fetal poles without fetal cardiac activity.…”
Section: Discussionmentioning
confidence: 70%
“…In at least 35-44% of patients, the factors inducing abortion are still unclear; these particular cases are now referred to as unexplained recurrent spontaneous abortion (URSA). However, it has recently been shown that URSA has features of an alloimmune disease associated with failure of the fetal-maternal immunologic tolerance (Christiansen et al, 2004;Kwak-Kim et al, 2010;Leber et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They are considered deleterious to the pregnancy by direct embryotoxic activity or by damaging the placental trophoblasts. Conversely, high concentrations of the anti-inflammatory cytokines IL-4, -6, -10, and -13 (Th2 type) are beneficial to the developing embryo by enhancing placental growth and function (53). Evidence exists that inter individual variation in the inflammatory cytokine response may affect the risk of unexplained recurrent pregnancy loss (RPL).…”
Section: D] Cytokines Factormentioning
confidence: 99%
“…. Nevertheless, abnormal inflammatory events may lead to adverse pregnancy outcomes, such as implantation failure, pregnancy loss, preeclampsia, preterm labour, intrauterine growth restriction (IUGR), and foetal inflammatory syndrome (Kwak-Kim et al, 2010). Disregulation of cell function mediators can simply derive from genetic conditions, with no need for infectious or inflammatory external stimuli.…”
Section: Direct and Indirect Relationship Between Inflammation And Prmentioning
confidence: 99%